Iman-restoration therapy (IRTI) : a new counseling approach and its usefulness in developing personal growth of Malay adolescents - Abdul-Razak, A.L.; Mohamad, M.; Alias, Alizi (2011)
Over the years, it has become a trend that those in mental health professions, especially counselors and psychologists are less religious, even atheistic due to their secular belief system. This is coupled with their diminutive efforts to link spirituality and science in most of their research works and intellectual frameworks in relation to counseling and treating psychological illnesses. However, it has been found in recent past that three quarters of counselors, even with secular and Christian belief system, reported using spirituality as an intervention tool in their research. This significant finding reflects the growing realization on the significance of religion and spirituality as an effective psychotherapeutic intervention. Thus, the purpose of this study is to examine ÔmÉn Restoration Therapy, a new psychotherapeutic approach which is based on the study of the Qur‟an, Sunnah and the works of early Muslim scholars, as a new counseling approach in developing personal growth of Malay adolescent clients. Through a single case study design, data was collected from interview and counseling sessions from an undergraduate student at the International Islamic University Malaysia (IIUM). With the emergence of seven themes, results revealed that maintaining ones faith in Allah SWT can bring about a positive functioning in one‟s cognitive, emotive, behavior and motivational components and attain spiritual intuition that fosters religious faith and meaningful living. Implications and suggestions for further studies are duly illustrated.